2017
DOI: 10.1111/jcpe.12844
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrushing behaviour and periodontal pocketing: An 11‐year longitudinal study

Abstract: This 11-year prospective study showed that toothbrushing behaviour was associated with smaller increments in the number of teeth with periodontal pocketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…A systematic review by Zimmermann et al . as well as a recent longitudinal study by Joshi et al . reported a negative association between frequent toothbrushing and periodontitis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A systematic review by Zimmermann et al . as well as a recent longitudinal study by Joshi et al . reported a negative association between frequent toothbrushing and periodontitis.…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review by Zimmermann et al 39 as well as a recent longitudinal study by Joshi et al 40 reported a negative association between frequent toothbrushing and periodontitis. However, there are also some contradicting findings like Lissau et al 41 and Elter et al 42 In our study, we found that boys and girls in different education levels seemed to gain differently from toothbrushing.…”
Section: Discussionmentioning
confidence: 99%
“…27 Good plaque control is crucial to maintain periodontal health, and data related to tooth brushing behavior supported this statement. 28,29,30 An 11-year study showed that tooth brushing was associated with a decrease in the number of teeth with periodontal pocketing. There was a clear dose-response relationship between tooth brushing frequency and change in the number of teeth with PPD ≥ 4 mm.…”
Section: Periodontal Treatmentmentioning
confidence: 99%
“…Frequency of tooth brushing was dichotomised as more than once a day versus once a day or less, as this cut-off has been commonly used in studies concerning tooth brushing and oral health (8,9) and since twice a day (morning and evening) is the official recommendation in Norway (35). However, the evidence supporting twice a day as the optimal frequency is inconsistent and limited (10,(36)(37)(38) and some describe this recommendation more as a social norm (37).…”
Section: Discussionmentioning
confidence: 99%
“…When diets include sugary foods and beverages, daily tooth brushing with fluoridated toothpaste is the main primary prevention against caries (6,7). Frequency of brushing has also been associated with periodontal disease (8)(9)(10), and with better health status in general (11)(12)(13)(14). However, the efficacy and long-term effects of brushing are not only influenced by the frequency, but frequency is usually emphasised (15) and may function as an indicator of children's oral hygiene (16).…”
Section: Introductionmentioning
confidence: 99%